A Map Out On the Symmetrical Life Cycle of Humans and Flowers through Cyber Literature - Narayanan, Anjana; Satheesh, Vaishnavi; Aich, Shibani Chakraverty (International Journal of Psychosocial Rehabilitation, 2020)
Flowers are associated with terms such as delicate, beautiful, and fragrant among other things. The transience of human life and flowers are fairly similar. This paper presents a view of the lives of two diverse and troubled individuals who are epitomized through flowers. Cyber literature is a new born among the varied genres of English Literature. This era of technological advancements help every single piece of literature to reach a wide spectrum of readers. This paper focuses on the personification of the sunflowers in the collection of poetry The Sun and Her Flowers by Rupi Kaur, popularly known as the Instagram poet and the enchanted rose in the Disney movie, Beauty and the Beast. Beauty and the Beast (1991) is based on the French fairy tale that concentrates on the life of a prince who is cursed by an enchantress and transformed into a monster. The Sun and Her Flowers (2017) is a poetry book that details the trials and tribulations the poet faces in her life, which she recites with the image of sunflowers. The paper is an attempt to entwine the idea of the different stages of a sunflower and human life, as expressed in The Sun and Her Flowers, with that of the Beast’s connection to the mystical rose. From wilting to revival, a flower’s life is identical to the essence of human life.